Implementation of a Public Works Communication Management Model - Miranda, Estefani R. (2023)
Conflicts between stakeholders during decision making in construction projects occur on a daily basis, as they often have an inadequate communications management, causing delays and cost overruns in the project. For this reason, alternative solutions were sought to reduce the percentage of delays due to decision-making conflicts. The proposal of this research focuses on the implementation of a collaborative software model in public works in its execution stage, this software allows the members of a work team, a fluid communication, as well as the instantaneous sharing of information. The software was implemented in a Peruvian company of small and medium contracting capacity, the process of elaboration of valorization was analyzed before the implementation of the software, that is to say, the elaboration in a traditional way, where it was obtained that the main events that generated delays were: Lack of access to the required documentation of the different areas of the project, Lack of updated documentation, Disagreement in the Quantity Takeoff and The non-delivery on time of reports. By implementing the software, the process of preparing the Valorization was reduced by 8 h.